2022
DOI: 10.1186/s12958-021-00880-4
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous mutation in SLO3 leads to severe asthenoteratozoospermia due to acrosome hypoplasia and mitochondrial sheath malformations

Abstract: Background Potassium channels are important for the structure and function of the spermatozoa. As a potassium transporter, the mSlo3 is essential for male fertility as Slo3 knockout male mice were infertile with the series of functional defects in sperm cells. However, no pathogenic variant has been detected in human SLO3 to date. Here we reported a human case with homozygous SLO3 mutation. The function of SLO3 in human sperm and the corresponding assisted reproductive strategy are also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It has been suggested that human KSper can be mediated by SLO1 [ 90 ], by both SLO1 and SLO3 [ 40 , 83 , 91 ] or by a human-specific SLO3 variant [ 15 , 24 , 84 , 119 ]. In this context, a recent study described a human case of male infertility in which a homozygous mutation in SLO3 causes severe asthenoteratozoospermia due to acrosome hypoplasia and mitochondrial sheath malformations [ 94 ]. Additionally, the differential characteristic of human KSper may be due to association with specific auxiliary subunits, which can produce profound changes in SLO channel gating properties [ 85 , 95 , 99 ].…”
Section: Sperm Capacitation and Hyperpolarizationmentioning
confidence: 99%
“…It has been suggested that human KSper can be mediated by SLO1 [ 90 ], by both SLO1 and SLO3 [ 40 , 83 , 91 ] or by a human-specific SLO3 variant [ 15 , 24 , 84 , 119 ]. In this context, a recent study described a human case of male infertility in which a homozygous mutation in SLO3 causes severe asthenoteratozoospermia due to acrosome hypoplasia and mitochondrial sheath malformations [ 94 ]. Additionally, the differential characteristic of human KSper may be due to association with specific auxiliary subunits, which can produce profound changes in SLO channel gating properties [ 85 , 95 , 99 ].…”
Section: Sperm Capacitation and Hyperpolarizationmentioning
confidence: 99%
“…Only recently, the screening of sub-fertile patients enrolled in ART confirmed the involvement of hSLO3 mutations in human asthenoteratozoospermia [ 48 ]. Indeed, a Chinese patient carrying the homozygous missense variant p.Ile413Phe showed male infertility due to impaired acrosome formation, mitochondrial dysfunction, altered membrane potential during capacitation and reduced sperm motility.…”
Section: Mutations In Ion Transporters and Channels That Results In H...mentioning
confidence: 99%
“…Geng et al found that human SLO3 is rapidly evolving and natural genetic variation (C382R) shows enhanced Ca 2+ sensitivities (Geng et al, 2017). Recently, Lv et al found an asthenoteratozoospermia case with SLO3 homozygous mutation, which leads to infertility, suggesting that functional SLO3 is indispensable for human fertility (Lv et al, 2022). Therefore, it has been confirmed that SLO3 plays important roles in human sperm.…”
Section: Discussionmentioning
confidence: 99%